Pharmacokinetic/Pharmacodynamic Correlation of Cefquinome Against Experimental Catheter-Associated Biofilm Infection Due to Staphylococcus aureus - Zhou, Yu-Feng; Shi, Wei; Yu, Yang; Tao, Meng-Ting; Xiong, Yan Q.; Sun, Jian; Liu, Ya-Hong (Frontiers in Microbiology, 2016)
Biofilm formations play an important role in Staphylococcus aureus pathogenesis and contribute to antibiotic treatment failures in biofilm-associated infections. The aim of this study was to evaluate the pharmacokinetic/pharmacodynamic (PK/PD) profiles of cefquinome against an experimental catheter-related biofilm model due to S. aureus, including three clinical isolates and one non-clinical isolate. The minimal inhibitory concentration (MIC), minimal biofilm inhibitory concentration (MBIC), biofilm bactericidal concentration (BBC), minimal biofilm eradication concentration (MBEC) and biofilm prevention concentration (BPC) and in vitro time-kill curves of cefquinome were studied in both planktonic and biofilm cells of study S. aureus strains. The in vivo post-antibiotic effects (PAEs), PK profiles and efficacy of cefquinome were performed in the catheter-related biofilm infection model in murine. A sigmoid Emax model was utilized to determine the PK/PD index that best described the dose-response profiles in the model. The MICs and MBICs of cefquinome for the four S. aureus strains were 0.5 and 16μg/mL, respectively. The BBCs (32-64 μg/mL) and MBECs (64-256 μg/mL) of these study strains were much higher than their corresponding BPC values (1-2 μg/mL). Cefquinome showed time-dependent killing both on planktonic and biofilm cells, but produced much shorter PAEs in biofilm infections. The best-correlated PK/PD parameters of cefquinome for planktonic and biofilm cells were the duration of time that the free drug level exceeded the MIC (fT>MIC, R2=96.2%) and the MBIC (fT>MBIC, R2=94.7%), respectively. In addition, the AUC24h/MBIC of cefquinome also significantly correlated with the anti-biofilm outcome in this model (R2=93.1%). The values of AUC24h/MBIC for biofilm-static and 1-log10-unit biofilm-cidal activity were 22.8 h and 35.6 h; respectively. These results indicate that the PK/PD profiles of cefquinome could be used as valuable guidance for effective dosing regimens treating S. aureus biofilm-related infections.